When the world feels like a scary place : essential conversations for anxious parents & worried kids - Gewirtz, Abigail H. (Workman Publishing, 2020)
"In our complicated world, big issues make both parents and children anxious. So how should parents talk to their kids about the things that make both parent and child on edge - from family financial issues to school shootings to global warming? Here, an expert child psychologist offers parents scripts for conversations that will help us raise kids who are informed, engaged, and confident."--Publisher's description.